Five Souls-Based Character Education at Tahfizul Quran Boarding School - Yusutria Yusutria; Hanif Cahyo Adi Kistoro; Yuherman Yuherman; Azwar Azwar (Faculty of Tarbiyah Universitas Islam Tribakti Lirboyo Kediri, 2022)
Pesantren prioritizes spiritual improvement and good character for students based on the five souls (panca jiwa). When the soul or mind is stable, it can automatically reveal good character and qualities. The value of the five souls is a combination of various crystallizations of pesantren values, which must be integrated and taught in all santri (Islamic Students) activities. Five souls are enthusiastically assimilated in doing all activities to awaken other positive characters. The discussion aims to find out the form of internalization of character education based on the five souls at the Tahfizul Quran Boarding School in West Sumatra. This research approach is the descriptive-qualitative approach. The discussion results showed that the five young souls are honest, independent, brotherly, and free spirits to prepare the concluding virtuous, noble, and meaningful individuals in better directions in life. Values were instilled by the following methods: the exemplary method, the habitual method, giving advice, methods of motivation and threats, methods of persuasion, and the story method. Supporting factors for implementing character education have good management performance, the active role of the kiai as the pesantren leader and the ustaz with high discipline. The obstacles are students' lack of awareness and willingness to follow the pesantren education system, the difficulty of adjusting to pesantren activities, and not all students being able to comply.